2022
DOI: 10.1186/s13024-022-00532-0
|View full text |Cite
|
Sign up to set email alerts
|

VCP suppresses proteopathic seeding in neurons

Abstract: Background Neuronal uptake and subsequent spread of proteopathic seeds, such as αS (alpha-synuclein), Tau, and TDP-43, contribute to neurodegeneration. The cellular machinery participating in this process is poorly understood. One proteinopathy called multisystem proteinopathy (MSP) is associated with dominant mutations in Valosin Containing Protein (VCP). MSP patients have muscle and neuronal degeneration characterized by aggregate pathology that can include αS, Tau and TDP-43. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Although even a small inhibitory effect on disaggregation may contribute to aggregate pathology in neurons over decades, the disease mutations may alternatively affect other steps during aggregate formation, including aggregate seeding and Tau degradation in cooperation with the proteasome. Indeed, an increase in intracellular aggregation is observed when VCP is inhibited in recipient cells at the time of seeding 64 or when VCP D395G is expressed in the recipient cells 21 . Note that we introduced the mutant VCP proteins in cells containing preexistent Tau aggregates to exclude a potential role of VCP in the process of aggregate seeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although even a small inhibitory effect on disaggregation may contribute to aggregate pathology in neurons over decades, the disease mutations may alternatively affect other steps during aggregate formation, including aggregate seeding and Tau degradation in cooperation with the proteasome. Indeed, an increase in intracellular aggregation is observed when VCP is inhibited in recipient cells at the time of seeding 64 or when VCP D395G is expressed in the recipient cells 21 . Note that we introduced the mutant VCP proteins in cells containing preexistent Tau aggregates to exclude a potential role of VCP in the process of aggregate seeding.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant proteins, carrying a C-terminal myctag, were transiently overexpressed in Tet-TauRD-Y* cells for 24 h, and then TauRD-Y synthesis was stopped with doxycycline to observe disaggregation. Note that mutant VCP was expressed in cells containing pre-formed aggregates to exclude a potential role of VCP in aggregate seeding 64 . The myc-tagged mutant proteins were present in hexamers that migrated on native PAGE like WT VCP (Supplementary Fig.…”
Section: Effects Of Vcp Mutants On Tau Disaggregationmentioning
confidence: 99%
“…These concepts can be leveraged using computational protein design to generate protein sequences that can bias these ensembles towards a more defined state compatible with a single fibrillar conformation and not compatible with other conformations. Applications of these designed "restrictive" sequences may allow selective amplification of these structures, using cellular systems of tau and other protein prion-like propagation 71,[78][79][80] offering avenues to diagnose disease based on conformation in premortem samples. These ideas may further inform the capacity of seed to propagate to promote pathology thus relating macroscopic properties such as the shape of protein inclusions in human tissues to molecular properties of the fibrillar structure.…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L1 and MAFG regulons both included genes involved in iron sequestration ( FTH1 and FTL ), and the protective ALS/bvFTD gene SQSTM1 (Figure 7B, C, Table S6). In addition, the MAFG regulon includes VCP , another ALS/bvFTD disease gene that reduces tau proteopathic seeding (Zhu et al, 2022), the PD risk gene SCNA , and genes involved in the regulation of selective autophagy, proteostasis, RNA stabilization, and synaptic vesicle exocytosis (Figure 7D). We confirmed that VCP expression is positively correlated with MAFG expression across EX in the insular cortex (Figure 7E).…”
Section: Resultsmentioning
confidence: 99%